A review on production, marketing and use of fuel briquettes - Asamoah, Bernice; Nikiema, Josiane; Gebrezgabher, Solomie A.; Odonkor, Elsie; Njenga, M. (International Water Management Institute, 2016)
Where modern heating and cooking fuels for domestic, institutional, commercial and industrial use are not readily available, briquettes made from biomass residues could contribute to the sustainable supply of energy. This study reviews the briquette making process, looking at the entire value chain starting from the type and characteristics of feedstock used for briquette making to the potential market for briquettes in developing countries. It also analyzes the role that gender plays in briquette production. Depending on the raw materials used and technologies applied during production, fuel briquettes come in different qualities and dimensions, and thus require appropriate targeting of different market segments. Key drivers of success in briquette production and marketing include ensuring consistent supply of raw materials with good energy qualities, appropriate technologies, and consistency in the quality and supply of the briquettes. Creating strong partnerships with key stakeholders, such as the municipality, financiers and other actors within the briquette value chain, and enabling policy are important drivers for the success of briquette businesses.